(3fJjLI GdCacGQ Phi GdeLO aj JMQjQ CHMGK (B( (3hHYO (B)s - (3eMeO GdRgGQ GdYRjRjs
(3ChdgG (B:s
(3ddg GdPi dg GdCeQ ef bHd hef HYO abO SCdfi CYR ENhGfi hChMO NdGfi Cf CVY dg QSGdI dWjaI JJVef CHMGK hHYO hSejJgG fJjLI CacGQ Phi GdeLO ai JMQjQ CHMGK hHYO s
(3BNQgG (B:s
(3aEf PcQJ ceG JbOe ai cdGe UGMH GdeaJGM JYjf chfgG ESJjfGajI Ch YGWaI ceG JbOe hgPG BNQ eG jSQ Gddg ef aVdg hefg Je s
(3HgG fXGe GdJYbjHIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs